Sustainable methodologies based on residue recovery for pH control in anaerobic digestion - Gameiro, Tânia Vanessa dos Santos (2021)
The main objective of this work was the study of the effect of the addition of alkaline inorganic residues (fly ash and red mud), incorporated in inorganic geopolymeric spheres, for pH control and improvement of anaerobic processes during the treatment of challenging organic wastes. In the first phase, the addition of fly ash to two different effluents was studied. It The effluent from the first bleaching stage of a pulp and paper industry was used, with high concentrations of low biodegradable organic compounds (AOX) and very low pH (≈ 2), as well as the by-product of a dairy industry (cheese whey), with high organic load and fast propensity to acidification under anaerobic conditions. The addition of fly ash allowed the reduction of AOX by 62 % and the removal of 65 % of organic matter from the bleaching effluent. On the other hand, the amount of fly ash added to cheese whey degradation process was insufficient to instigate the methanogenic phase, thus leading to high concentrations of volatile organic acids and low methane productivity. In the second phase, it was studied the addition of geopolymeric spheres, with fly ash in their constitution, to discontinuous and semi-continuous anaerobic digesters for the treatment of cheese whey, which has a greater biodegradation potential. The addition of spheres with a greater amount of ash (FA-based) in its constitution obtained better productivity in terms of methane. It was also found that the increase in the number of spheres boost the production of methane by about 30 %. In addition, the porosity and concentration of the spheres influences anaerobic performance. Higher amounts and greater porosity of the spheres improve methane production by 82 %, even after 2 consecutive substrate additions, compared to the addition of chemical alkalinity. With 4 sequential additions of substrate, the system with FA-based spheres with high porosity achieved also a very good performance in terms of pH stabilization in the digester and achieved a methane yield improvement of 8 %. In the third phase, it was studied the addition of geopolymeric spheres, with red mud in their constitution (RM-based), to semi-continuous anaerobic digesters for the treatment of cheese whey. With the increase of the organic load, the anaerobic systems were temporarily inhibited, recovering after a longer period. The difference in performance between digesters with the addition of chemical alkalinity and the addition of RM-based geopolymeric spheres was evident after inhibition by the substrate accumulation. The spheres promoted a prolonged and slow leaching of alkalis, promoting greater stability of the system and improving the production of methane by 94 % and the organic matter removal by 44 %. After being used in anaerobic digesters, the spheres keep their integrity and can be recovered and reused in other applications, such as pollutant adsorbents or integrated into cements and mortars. With this study, it can be concluded that the use of inorganic geopolymeric spheres is an innovative and very promising strategy for pH control and to promote the stability of anaerobic processes, thus contributing to the concept of circular economy, using wastes (cheese whey, fly ash and red mud) in biological processes, for their valorization into new products (geopolymeric spheres) and energy (methane).